2022
DOI: 10.3390/antibiotics11050616
|View full text |Cite
|
Sign up to set email alerts
|

Salphage: Salvage Bacteriophage Therapy for Recalcitrant MRSA Prosthetic Joint Infection

Abstract: Prosthetic joint infections are a devastating complication of joint replacement surgery. Consequently, novel therapeutics are needed to thwart the significant morbidity and enormous financial ramifications that are associated with conventional treatments. One such promising adjuvant therapeutic is bacteriophage therapy given its antibiofilm activity and its ability to self-replicate. Herein we discuss the case of a 70-year-old female who had a recalcitrant MRSA prosthetic knee and femoral lateral plate infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Doub et al. reported results from a treatment of a prolonged MRSA prosthetic knee infection with the phage Mallokai [ 53 ]. The authors pointed out that a testing of the phage prior to therapeutic application indicated the absence of endotoxins.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Doub et al. reported results from a treatment of a prolonged MRSA prosthetic knee infection with the phage Mallokai [ 53 ]. The authors pointed out that a testing of the phage prior to therapeutic application indicated the absence of endotoxins.…”
Section: Resultsmentioning
confidence: 99%
“…Growth inhibition assays confirmed the lytic killing by the same phage as independent of the particular morphology. Still, it is highlighted that the possibility of multiple colony morphologies should be met with the verification of broad enough efficacy of the phages [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therapeutic potential of phages in the long-term largely depends on their activity against clinically relevant strains. Staphylococcus phages have already reached the level of clinical trials and are being used to treat infections in the context of expanded use, demonstrating their therapeutic potential and efforts to further develop this field ( Lehman et al., 2019 ; Doub et al., 2020 ; Ferry et al., 2020 ; Van Nieuwenhuyse et al., 2021 ; Doub et al., 2022 ). Phages isolated in this study, COP-80A, COP-80B, and COP-110, infect the majority of S. epidermidis strains tested and also other coagulase-negative strains from our collection, similar as observed for phages phiIPLA-C1C and SEP1 ( Melo et al., 2014 ; Gutiérrez et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%